2015
DOI: 10.1002/cphc.201500194
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Driven Reversible Alignment Switching of Liquid Crystals Enabled by Azo Thiol Grafted Gold Nanoparticles

Abstract: Stimuli-directed alignment control of liquid crystals (LCs) with desired molecular orientation is currently in the limelight for the development of smart functional materials and devices. Here, photoresponsive azo thiol (AzoSH) was grafted onto gold nanoparticles (GNPs). The resulting hybrid GNPs were able to homogeneously mix with a commercially available nematic LC host, as evidenced by Cryo-TEM. Interestingly, the LC nanocomposites were found to undergo reversible alignment transition upon light irradiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…However, the underlying mechanisms responsible for such extraordinarily large non-linearity are still not clear. For example, such self-activated switching effects have been also observed in other azobenzene LCs, where the laser-induced photothermal effects and trans-cis isomerism are responsible for orientation disorder of director axis and birefringence modification [60][61][62][63][64].…”
Section: Dye-doped Nematic Liquid Crystalsmentioning
confidence: 89%
“…However, the underlying mechanisms responsible for such extraordinarily large non-linearity are still not clear. For example, such self-activated switching effects have been also observed in other azobenzene LCs, where the laser-induced photothermal effects and trans-cis isomerism are responsible for orientation disorder of director axis and birefringence modification [60][61][62][63][64].…”
Section: Dye-doped Nematic Liquid Crystalsmentioning
confidence: 89%
“…[329] Due to the nonradiative relaxation of longitudinal surface plasmon resonances (LSPR), the M-GNRs could convert the external NIR light irradiations into localized heat, i.e., photothermal effect. [330][331][332][333] Thanks to the excellent thermoresponsive properties of BPs, their 3D nanostructures could be manipulated with the "photothermal effect" of M-GNRs. It was found that introducing M-GNRs into BPs enabled not only the stabilization of the cubic nanostructure, but also the reversible transformations of 3D nanostructures between BCC and SC symmetry as well as dynamic RGB reflections upon NIR irradiation at 808 nm.…”
Section: Blue Phase Liquid Crystalsmentioning
confidence: 99%
“…Very recently, Xue et al, reported photoresponsive azo thiol grafted gold nanoparticles for stimuli-directed alignment control of LCs [50]. In this paper, we report a new series of thiolated azobenzene molecules embedded to gold NPs which exhibit nematic and SmA phases irrespective of chain length and parity.…”
Section: Introductionmentioning
confidence: 91%